KARAKTERISTIK STRUKTUR ANATOMI DINDING SEL JABON MERAH (Anthocephalus macrophyllus) PROVENANSI WAJO - Nurul Muhlisah Mompewa; Andi Detti Yunianti; Siti Halimah Larekeng (PERENNIAL, 2019)
Apart from being a key to identifying wood, the characteristics of the anatomical structure of cell walls can be used as a reference in determining the quality of wood, especially for its use. However, the characteristics of wood in the same species are sometimes found to be different due to the growing place is unidentical. Therefore, this study aimed to identify the cell wall characteristics of Jabon Merah wood from Wajo provenance. The wood was collected from Tangkoro Village, Pitumpanua District, Wajo Regency, South Sulawesi. It was then prepared in slicing and maceration samples. The structures of cell walls observed in the preparations were a pit, perforation plate, and tylosis. The results showed the Jabon Merah had inter vessel pit and perforation plate types, namely polygonal alternating and scalariform, respectively. Also, it had a tylosis in the vessel.